Roar! Tyrannosaurus Rex (Scholastic Singapore, 2013)
Do not miss the dinosaur hard book series Imagine the ancient dinosaurs lifelike in the hands of children, will bring much surprise! do you know? The first complete thunder fossil was discovered in 1909 in Utah, USA, and now it became a dinosaur national sanctuary. The most surprising is that the body of the huge thunder, brain capacity is smaller than the kitten! This set of tens of thousands of dinosaur hard pages can not be missed, a total of four, respectively, introduced Lei Long, Triangle Dragon, Tyrannosaurus and Jianlong, each with dinosaurs as a cover picture, vivid and mighty image. Which describes the dinosaurs related knowledge, such as the dinosaur survival of the age, size and physical characteristics, characteristics and strengths, survival habits and so on. Each page is accompanied by a small knowledge of the dinosaurs that make the child wonder. This book is suitable for children, or parents of teachers to accompany children over five years old read.